Application of Compound Two Times Quenching Heat Treatment in Roller Chain Drive - Shang Zhaohua; Wang Shungong; Liu Depeng; Qin Na (Jixie chuandong, 2016)
The roller chain pin shaft heat treatment process is studied and improved,by using the compound two times chemical heat treatment method,the hardness on the surface of the pin and the thickness of hard floors are improved,and the solubility of the pin shaft and sleeve on the surface is avoided. Through the improvement of heat treatment,the wearability of the chain is significantly improved.